Sodium butyrate attenuated diet-induced obesity, insulin resistance and inflammation partly by promoting fat thermogenesis via intro-adipose sympathetic innervation - Zhu, Wanlong; Peng, Ke; Zhao, Yan; Xu, Changjing; Tao, Xuemei; Liu, Yuanzhi; Huang, Yilan; Yang, Xuping (Frontiers in Pharmacology, 2022)
Emerging evidence suggests that butyrate, a short-chain fatty acid, may have beneficial effects on obesity and its associated metabolic comorbidities, but the related molecular mechanism is largely unknown. This study aims to investigate the role of butyrate in diet-induced obesity and metabolic disorders and the relevant regulatory mechanisms. Here, dietary supplementation with Sodium butyrate (NaB) was carried out in mice fed with a high-fat diet (HFD) or chow diet. At week 14, mice on HFD displayed an obese phenotype and down-regulated expression of thermogenic regulators including Ucp-1 and Pgc-1α in adipose tissue. Excitingly, NaB add-on treatment abolished these detrimental effects. Moreover, the obesity-induced insulin resistance, inflammation, fatty liver, and intestinal dysfunction were also attenuated by NaB administration. Mechanistically, NaB can promote fat thermogenesis via the increased local sympathetic innervation of adipose tissue, and blocking the β3-adrenergic signaling pathway by 6-hydroxydopamine abolished NaB-induced thermogenesis. Our study reveals a potential pharmacological target for NaB to combat obesity and metabolic disorders.